(untitled) (Journal of The Colloquium for Information Systems Security Education, 2022)
Cybersecurity pedagogical approaches do not address the challenges faced by students with English as an additional language (EAL). Despite EAL students representing a critical labour force for this important global and multidisciplinary industry, there lacks both research and cohesive solutions to address this issue. Via student interviews and semi-thematic analysis, this paper demonstrates that EAL cybersecurity students express challenges with aspects of cybersecurity content. Secondly, it is shown that predominant cybersecurity education bodies of knowledge and frameworks do not address challenges faced by EAL cybersecurity students.